'Horse Race, Rich in Woes': Orestes' Chariot Race and the Erinyes in Sophocles' Electra. (November 2021) - Johnston, Alexandre
Abstract: This article offers a new, ironic reading of the false narrative of Orestes' chariot accident in Sophocles' Electra (680–763). It argues that the speech exploits an established connection between the ancestral evils of the Atreids and the thematic nexus of horses, chariot racing and disaster to evoke Orestes' flight from the Erinyes following the matricide. Focusing on the language and structure of the narrative as well as drawing on other versions of the story (notably the surviving plays by Aeschylus and Euripides), the article demonstrates, in contrast to previous readings, that the speech is much more than an over-elaborate means to an end. Instead, in an ominous and profoundly ironic twist, the Paedagogus' fictional narrative of the chariot race offers a possible vision of the trials awaiting the real Orestes. The matricide and murder, far from ending the ancestral woes of the Atreids, may well bring about Orestes' pursuit by the Erinyes.